Utilizing Facebook And Instagram (Facegram) To Create A Digital Learning Program For Integrated English Skills - Mahmud, Murni; Burhamzah, Muftihaturrahmah; Amin, Fatimah Hidayahni (ELT Worldwide: Journal of English Language Teaching, 2023)
The objective of this study is the development of a digital educational tool for English language instruction by utilising social media platforms, specifically Facebook and Instagram. The ADDIE (Analyse, Design, Develop, Implement, and Evaluate) paradigm, developed by Gagne et al. in 2005, was employed in the research and development (R&D) project under consideration. The primary objective of this study is to demonstrate the process of creating a digital learning module for Integrated English Skills (IIC) education by utilising social media posts from Facebook and Instagram (FaceGram). Facebook and Instagram, because to their nature as social media platforms, are perceived as attractive resources for the purpose of facilitating Integrated English Skills instruction. The utilisation of Facebook and Instagram as platforms for English language training is anticipated to undergo a transformative process, resulting in a pedagogical approach that is both intellectually stimulating and distinctively innovative. This study aims to enhance the four English language skills, namely writing, speaking, reading, and listening, through the utilisation of Facebook and Instagram posts as educational resources. This study aims to provide several illustrative instances of information sourced from Facebook and Instagram that can be effectively utilised for the purpose of instructing Integrated English Skills within the context of digital learning. The present study employed a survey methodology within the English Literature Programme at Universitas Negeri Makassar. The participants consisted of students enrolled in the Integrated English Skills course. The findings of this study could serve as a valuable resource for educators of English as a second language, enabling them to develop engaging and distinctive instructional materials.